(untitled) (Research, Society and Development, 2022)
Mammoplasty is the most performed plastic surgery on a global scale, being intensely stimulated by the extensive dissemination on social media and the gradual change in beauty standards, which currently aim for breasts with greater volume and projection. However, this procedure carries risks of negative outcomes, often not informed to patients. The present study aims to collect data on the quality of information given to patients undergoing mammoplasty, focusing on complications that may occur in the postoperative period. The study was carried out in two phases: the first through a literature review with scientific data from 2011 to 2022. The second phase was based on the collection of data from patients who underwent the surgical procedure, through filling of online form. The survey had 40 questionnaires sent back to the researchers, of which 17.5% (n = 7) had to be excluded from the analysis. Among the interviewees, 33% did not know or did not receive the Free and Informed Consent Form and 67% received it. As for the information vehicles consulted, the main ones were plastic surgeons (90%, n = 30), people who had the same surgery (85%, n = 28) and the internet (70%, n = 23). It is concluded that there was a failure on the part of plastic surgeons to correctly instruct patients and to reinforce the importance of an active and attentive reading of the Free and Informed Consent Form. However, the procedure positively impacted the quality of life of these women.